Relationship Between Ultra-Processed Food Consumption and Cognitive Function among Children Ages 7-11 in Terengganu, Malaysia - Zulkornain, Shazwina Aqmar Fatnin; Ali, Asma'; Zakaria, Noor Salihah; Kamarudin, Khairil Shzamin; Jan Mohamed, Hamid Jan; Zainuddin, Ahmad Ali; Mohd Yusof, Hayati (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
This study aimed to examine the correlation between Ultra-Processed Foods (UPF) consumption and cognitive function among school-aged children (7–11 years) in Terengganu. A cross-sectional study (n=200; 53.5% girls; ages: 7–8y 13.0%, 9y 11.0%, 10y 17.0%, 11y 59.0%) was employed. Two non-consecutive 24-h recalls (one weekday, one weekend) were coded and foods classified with NOVA; UPF intake expressed as % of total energy. Cognitive function was assessed with Raven’s Coloured Progressive Matrices. Spearman’s correlation tested UPF–cognition associations (α=0.05). Mean energy intake was 1,623 kcal/day, approximating 84–101% of Malaysian Recommended Nutrient Intakes (RNI) across ages 7–11. UPFs contributed 26.7% of energy (weekday 25.8%, weekend 27.4%). Mean cognitive score was 105.4±18.7, with 28.5% in the average range. No significant correlation was observed between UPF energy share and cognitive scores (rs=0.065, p=0.361). While moderate UPF consumption did not directly impair cognitive function, this study reveals a compelling narrative about the protective role of traditional diets and parental involvement in shaping children's health and cognitive development.